2015
DOI: 10.1007/s40515-015-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Lignin and Fly Ash in Stabilizing Black Cotton Soil

Abstract: Subgrade is one of the important layers of any pavement. It must be able to support loads transmitted from pavement structure without excessive deformation under adverse climatic and traffic conditions. In this investigation, laboratory studies were carried out to evaluate the influence of a commercial electrolyte lignin stabilizer (ELS), fly ash (FA) and a combination of both, on black cotton (BC) soil procured from North Karnataka region in India. Basic geotechnical and engineering properties like unconfined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In this study, it was found that 20 % of fly ash is the optimum percentage. Many other studies concluded similar results by the addition of approximate percentages of fly ash [11][12][13].…”
Section: Literature Reviewmentioning
confidence: 58%
“…In this study, it was found that 20 % of fly ash is the optimum percentage. Many other studies concluded similar results by the addition of approximate percentages of fly ash [11][12][13].…”
Section: Literature Reviewmentioning
confidence: 58%
“…The test matrix of constant-amplitude fatigue loading tests is given in Table 3. The maximum stress were from 1/2 to 3/4 fractions of UCS values referring to Lekha et al [45], corresponding to medium to high stress levels. The UCS for each treatment condition was used as a basis for the calculation of fatigue stresses (e.g., r m , r a , r max , and r min ).…”
Section: Fatigue Loading Testsmentioning
confidence: 97%
“…After compaction, the samples were extruded out of the mould as shown in Figure 1 and cured in a controlled environment (60% relative humidity and 20 • C). A curing period of 14 days was adopted as the growth rate of mechanical strength was observed to be lowered after 14 days [12,23,68]. The UCS test were conducted under the strain-controlled condition at a loading rate of 1.5%/min in accordance with ASTM D2166 at the end of 14-day curing period.…”
Section: Experimental Scheme and Sample Preparationmentioning
confidence: 99%